2017
DOI: 10.1007/s00425-017-2838-x
|View full text |Cite
|
Sign up to set email alerts
|

Oryza sativa salt-induced RING E3 ligase 2 (OsSIRP2) acts as a positive regulator of transketolase in plant response to salinity and osmotic stress

Abstract: A rice gene (OsSIRP2) encoding the RING Ub E3 ligase was highly induced under salinity stress and physically interacted with a transketolase (OsTKL1). Overexpression of OsSIRP2 conferred salinity and osmotic stress tolerance in plants. The RING E3 ligases play a vital role in post transitional modification through ubiquitination-mediated protein degradation that mediate plants responses during abiotic stresses and signal transduction. In this study, we report an Oryza sativa salt induced Really Interesting New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Rice expresses many RING finger E3 ligases that are involved in salt stress regulation, such as the SALT-INDUCED RING PROTEIN family (SIRP) [ 123 , 124 , 125 , 126 ] ( Figure 4 ). Three of the four members have been described as negative regulators of salinity stress responses [ 123 ].…”
Section: Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice expresses many RING finger E3 ligases that are involved in salt stress regulation, such as the SALT-INDUCED RING PROTEIN family (SIRP) [ 123 , 124 , 125 , 126 ] ( Figure 4 ). Three of the four members have been described as negative regulators of salinity stress responses [ 123 ].…”
Section: Salt Stressmentioning
confidence: 99%
“…On the other hand, overexpression of OsSIRP2 E3 ligase enhances resistance towards salt and osmotic stress in Arabidopsis [ 124 ]. Yeast two-hybrid (Y2H) and pulldown assays have demonstrated physical interaction between OsSIRP2 and a potential target, O. sativa TRANSKETOLASE 1 (OsTKL 1 ) [ 124 ].…”
Section: Salt Stressmentioning
confidence: 99%
“…A total of 474 RING domains have been identified in 469 potential proteins encoded in the tomato ( Solanum lycopersicum ) genome (Yang et al, 2019). However, the functional studies of RING E3 ubiquitin ligase genes in tomato are very limited (Chapagain et al, 2018; Cho et al, 2017; Kim et al, 2019; Qi et al, 2020; Yang et al, 2019). Previously, we screened out a tomato RING‐type E3 ubiquitin ligase gene, SlRING1 , which was highly expressed in tomato roots in response to Cd stress (Qi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oryza sativa salt-induced RING finger protein 2 (OsSIRP2) is induced by high salinity, drought, and ABA and encodes a RING-type E3-ubiquitin ligase that localizes to the nucleus of rice protoplasts under both control and high-salinity conditions. OsSIRP2, when overexpressed in Arabidopsis, is shown to confer tolerance to salinity and osmotic stresses (Chapagain et al, 2018). It is also shown that OsSIRP2 is able to interact with the rice transketolase 1 (OsTKL1) in the cytoplasm, targeting it for degradation via the UPS.…”
Section: E3-ubiquitin Ligases In Salinity Responsesmentioning
confidence: 99%